1998
DOI: 10.1002/(sici)1099-0682(199804)1998:4<465::aid-ejic465>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Boryl- and Bridging Boryleneiron Complexes from Aminodichloroboranes

Abstract: Depending on the nature of the amino group bound to the boron atom, the reactions of various aminodichloroboranes R2NBCl2 with Na[(η5‐C5R′5)Fe(CO)2] yield either boryl or bridging borylene complexes of iron. The compounds [(C5R′5)(CO)2Fe{BCl(NR2)}] (1a, C5R′5 = C5H5, R = Me; 1b, C5R′5 = C5H4Me, R = Me; 1c, C5R′5 = C5Me5, R = Me) and [(η‐BNR2)(μ‐CO){(C5R′5)Fe(CO)}2] (2a, C5R′5 = C5H5, R = SiMe3; 2b, C5R′5 = C5H4Me, R = SiMe3) were isolated as orange (1a−c) or red (2a, b) crystalline solids, and characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
11

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 37 publications
1
33
2
11
Order By: Relevance
“…The outstanding preparative versatility of this route has led to a vast range of organometallic species so far, most of which have been obtained from group 13 [4][5][6][7][8][9][10][11][12][13][14][15] and group 14 precursors [16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The outstanding preparative versatility of this route has led to a vast range of organometallic species so far, most of which have been obtained from group 13 [4][5][6][7][8][9][10][11][12][13][14][15] and group 14 precursors [16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 58%
“…The molecule shows a four-legged piano-stool geometry with a large Mo-Sn distance of 2.8546(3) Å which is comparable to that of related molybdenum stannyl complexes such as ½fFeðg 5 -C 5 H 5 ÞðCOÞ 2 g 2 fMoðg 5 -C 5 H 5 ÞðCOÞ 3 gSnCl [22]. The SnMe 3 ligand adopts a staggered conformation with respect to the ½Moðg 5 -C 5 H 5 ÞðCOÞ 3 fragment as indicated by a dihedral angle Cp Cent -Mo-Sn-C6 of 175.39°.This orientation together with the large Mo-Sn separation allows for rather acute Sn-Mo-C(O) angles of 68.48(6) and 69.42 (8)°compared to the (O)C-Mo-C(O) angles of (79.30 (9) and 81.18(9)°). The coordination sphere around the tin atom displays angles from 106.97(7) to 112.40(7)°, whereby the small deviation from the ideal tetrahedral geometry is presumably caused by packing effects within the unit cell (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe1B1 and Fe2B2 bond lengths are 1.98(2) and 1.842(12) Å, respectively. These are considerably shorter than that found in the boryl complex [CpFe(CO) 2 BPh 2 ] (2.034(3) Å)46 and bridged borylene complex [(η‐BN(SiMe 3 ) 2 )(μ‐CO){Cp + Fe(CO)} 2 ] (2.007(3) and 2.002(3) Å) (Cp + =(η 5 ‐C 5 H 4 Me)) 47…”
Section: Resultsmentioning
confidence: 78%
“…This same research group prepared [202] amino-substituted boryl complexes of Fp by reacting dimethyl aminodichloroborane and di(trimethylsilyl)aminodiborane with the Fp anion To study if the ferrocenyl(bromo)boryl group could serve as a probe for the presence of any significant Fe-B -bonding, Braunschweig and coworkers synthesized and characterized Fp[B(Fc)Br] (Scheme 142) [206]. By comparing the crystal structure of this complex and its Fp* (C 5 Me 5 Fe(CO) 2 ) analog, these researchers concluded that the differences in steric bulk of the 5 -C 5 R 5 (R = H or Me) in the Fp ligands, affects the orientation and thus its -bonding.…”
Section: Fe-hg Bond Formationmentioning
confidence: 95%